Developing AR-based mathematics learning media on curved-surface solids using Assemblr Edu - Ilham Hafizt; Ade Mirza; Nurfadilah Siregar; Dede Suratman; Revi Lestari Pasaribu (Universitas Ahmad Dahlan, 2026)
This study addresses the lack of student interest in curved-surface solids and the limited use of instructional media in mathematics classrooms. It aimed to develop valid and engaging Augmented Reality-based learning media using Assemblr Edu specifically for this topic. Employing a Research and Development (R&D) approach following the ADDIE model, the study evaluated through two separate validations, which consisted of expert validation sheets completed by media expert and subject-matter experts, while student responses were collected using a response questionnaire. The validation results showed that three media experts produced an average score of 90% (highly valid), and three content experts provided an average of 91.43% (highly valid). Student responses from 30 participants showed a positive rate of 82.60% (very positive). These findings indicate that the AR-based media developed with Assemblr Edu is valid and received very positive responses from students. It is recommended that future studies apply this AR media to broader instructional topics while considering technical and accessibility factors.